Factors Influencing Rice Import Activities in Indonesia - Wali Akbar; Heru Subiyantoro; Machfud Sidik (Ekonomis: Journal of Economics and Business, 2023)
Rice is a very important commodity because it is consumed by the majority of the Indonesian population. Apart from being a source of carbohydrates, two-thirds of the calorie needs are obtained from rice. Rice is one of the most needed foods and is used as a staple food in Indonesia. It is undeniable that from the past and even in the future, humans need food to survive. The type of research used is Quantitative, namely the research method is a scientific approach to economic decisions. Based on the analysis and discussion of research results using multiple linear regression tests regarding the analysis of factors influencing rice imports in Indonesia, it can be concluded as follows: 1) The results of the study show that local rice variables, rice production and population partially have a significant effect on imports rice in Indonesia; 2) The results of the study show that the variables of local rice, rice production and population together have a significant effect on rice imports in Indonesia; 3) The results of the study state that the variables of rice consumption, rice stocks, domestic rice prices, and international rice prices have a positive and significant influence on rice imports in Indonesia with a confidence level of α 95%. Meanwhile, food is a very important term for agriculture, because food is one of the most basic human needs. Therefore, food scarcity can lead to economic vulnerability and social unrest.